Assessing the Effects of Fiscal Policies on Poverty and Inequality : The Case of Uruguay - Bucheli, Marisa (World Bank, Washington, DC, 2020)
This study looks at the redistributive effects of fiscal policy -- in particular of direct taxation and expenditures -- in Uruguay. This fiscal incidence analysis applies a widely recognized methodology to household survey data and government data for fiscal year 2017 and compares the results with the policies seen in 2009 to study the evolution of the distributional impacts of fiscal policy in the country. The study finds evidence that Uruguayan fiscal policy continues to reduce inequality, with government expenditures in the form of in-kind transfers leading to the largest decreases. While expenditures in basic education are benefitting the poorest, expenditures in tertiary education remain largely regressive. The personal income tax is found to be largely progressive, with the top quintile paying more than four-fifths of this tax. Uruguay’s fiscal policies also lead to a reduction in poverty, mainly due to well-targeted direct transfers.